(untitled) (Bangladesh Veterinarian, 2018)
Ram semen was assessed for quality and presence of bacteria. Four ejaculates were collected from each of four rams twice a week using artificial vagina. The volume varied from 0.4 - 1.3 mL, colour from 2 - 4 (creamy to creamy-grey), mass activity from 3 - 5, sperm motility from 75 - 85%, viability from 80 - 95%, and concentration from, 2500 - 5000 × 106/mL. The mass activity of ram R6 was significantly (P<0.05) higher (5.0 ± 0.0) compared with ram R1 (4.4 ± 0.5), R2 (3.9 ± 0.0) and R5 (4.7 ± 0.5). The mean motility was 81.7 ± 4.0, viability 90.0 ± 4.0 and concentration 3519.0 ± 545.6 x 106/ml. E. coli and Staphylococcus spp. were found in all four rams’ fresh semen confirmed by culture, staining and biochemical tests. However, Bacillus spp. was found only in ram R5. When the semen samples were treated with antibiotics there was no growth of bacteria after three days of incubation. It is suggested antibiotics control the transmission of microorganisms through AI in ewes. Bangl. vet. 2017. Vol. 34, No. 1, 20-26